A Novel Case of Drug Reaction With Eosinophilia and Systemic Symptoms (DRESS) Secondary to Acalabrutinib - Kirsten M. Johnson; Adam S. Kittai; Abraham M. Korman (Annals of Internal Medicine: Clinical Cases)
Here we describe an unusual case of a patient with chronic lymphocytic leukemia who developed drug reaction with eosinophilia and systemic symptoms from the Bruton kinase inhibitor acalabrutinib and propose a mechanism by which this class of medications may increase the potential for developing such reactions in this patient population. Drug reaction with eosinophilia and systemic symptoms has not been described previously in association with Bruton kinase inhibitors, which are known to target B cells.